Οι οικονομικές διαστάσεις των δημογραφικών εξελίξεων στη Θεσσαλία του 15ου αιώνα - ΤΕΡΕΖΑΚΗΣ, ΓΕΩΡΓΙΟΣ Ε. (Byzantina Symmeikta, 2021)
This is a study of the society of Thessaly in the 15th century focusing on the population distribution in the area. The examination of the economic data testifies an agricultural production – particularly grain and vineyards – as well as the growing importance of crafts and trade. There is, also, evidence about rice cultivation, which was probably introduced to the area by the Ottomans. Two reasons have been proposed regarding the introduction of rice cultivation in the area: a) it was the result of an official policy for the supply of the palace and the army; b) there was a high demand for rice, especially among the urban Muslim population, as most rice-fields were located near cities with strong Muslim communities. This underlines a strong correlation between political, economic and demographic development